1996
DOI: 10.1007/bf00333718
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton-induced unicell-colony transformation in Scenedesmus acutus and its effect on growth of herbivore Daphnia

Abstract: The effects of colonial ecomorphs of the green alga Scenedesmus acutus on growth of Daphnia cucullata and D. pulex were examined. In ecologically relevant densities (up to 200 animals l) the relatively small D. cucullata did not induce colony formation in Scenedesmus acutus, whereas the larger congener D. pulex significantly promoted colony formation. Both clearance rate and population growth rate (r) were significantly lower in D. cucullata when fed colonial Scenedesmus then when fed unicellular food. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 27 publications
2
86
1
Order By: Relevance
“…Obviously, when the colonies become very large or heavily spined they are a food source of lower quality for the zooplankters (Hessen & van Donk, 1993). When comparing single cells and coenobia of S. obliquus, Lampert et al (1994) found no differences in the uptake between colonies and single cells by Daphnia magna, nor did Lürling (1996) for D. pulex. However, the smaller species D. cucullata seemed to have problems with the colonies.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Obviously, when the colonies become very large or heavily spined they are a food source of lower quality for the zooplankters (Hessen & van Donk, 1993). When comparing single cells and coenobia of S. obliquus, Lampert et al (1994) found no differences in the uptake between colonies and single cells by Daphnia magna, nor did Lürling (1996) for D. pulex. However, the smaller species D. cucullata seemed to have problems with the colonies.…”
Section: Discussionmentioning
confidence: 90%
“…However, the smaller species D. cucullata seemed to have problems with the colonies. It seems to be the case that especially smaller Daphnia species, or juveniles of larger species have some problems with larger cells (in the case of Staurastrum), spined cells (Desmodesmus), or with colonies (Lürling & van Donk, 1996). However, the ecological relevance of this is difficult to assess, especially as the results in the literature are not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Keywords : clearance rate, food quality, grazing, induced defence, morphology, plankton interactions Aquatic Ecology & Water Quality Management, Department of Environmental Sciences, Wageningen University, PO Box 8080, NL-6700DD Wageningen, The Netherlands von Elert 2002), and morphology, such as cell wall thickening ) and colony formation (Lürling & Van Donk 1996). In the vast majority of these studies the alga used was Scenedesmus, which is known for its extreme morphological variability (Trainor 1998).…”
Section: Lürlingmentioning
confidence: 99%
“…(Hessen and van Donk, 1993;Lampert et al, 1994;Lu¨rling and van Donk, 1996). Colony formation also did not lead to any decline at PS II efficiency of algae.…”
Section: Introductionmentioning
confidence: 95%
“…Hessen and van Donk (1993) discovered the grazing from Daphnia could induce colony formation in green alga Scenedesmus subspicatus. As most grazers are size selective, this enlarged-volume defense reaction could reduce their predation risk from small Daphnia magna (Hessen and van Donk, 1993) and Dahpnia cucullata (Lu¨rling and van Donk, 1996).…”
Section: Introductionmentioning
confidence: 99%